Conduction system pacing learning curve: Left bundle pacing compared to His bundle pacing. (February 2023) - O'Connor, Matthew; Shi, Rui; Kramer, Daniel B.; Riad, Omar; Hunnybun, Daniel; Jarman, Julian W.E.; Foran, John; Cantor, Emily; Markides, Vias; Wong, Tom
Highlights: Left bundle branch area pacing has a shorter learning curve compared to His bundle pacing. The learning curve for left bundle branch area pacing is short and appears to plateaux after the first 10 cases for operators with prior CRT experience. Overall procedure duration and fluoroscopy time are both lower with left bundle branch area pacing compared to His bundle pacing. Abstract: Introduction: Conduction system pacing (CSP), consisting of His bundle pacing (HBP) or left bundle branch area pacing (LBBAP) is a rapidly developing field. These pacing techniques result in single lead left ventricular resynchronisation. Understanding of the associated learning curve of the two techniques is an important consideration for new implanters/implanting centres. Methods: We conducted a review of the first 30 cases of both HBP and LBBAP at The Royal Brompton Hospital. The procedural duration and fluoroscopy time were used as surrogates for the learning curve of each technique. Results: Patient characteristics were similar in HBP and LBBAP groups; LV ejection fraction (46% vs 54%, p = 0.08), pre-procedural QRS duration (119 ms vs 128 ms, p = 0.32). Mean procedural duration was shorter for LBBAP than for HBP (87 vs 107mins, p = 0.04) and the drop in procedural duration was more marked in LBBAP, plateauing and remaining low at 80mins after the initial 10 cases. Fluoroscopic screening time mirrored procedural duration (8 min vs 16 min, p < 0.01). Discussion/Conclusion: Our data suggest that the CSP learning curve was shorter for LBBAP than for HBP and appears to plateaux after the first 10 cases, however the HBP learning curve is longer with continued improvement over the first 30 cases. The shorter learning curve of LBBAP in conjunction with the superior electrical parameters and simplified programming mean the establishment of a CSP program is potentially easier with LBBAP compared to with HBP.